Lower limbs edema among medical students - Monika Załęcka; Kacper Lipiński; Aleksandra Królikowska (University of Applied Sciences in Tarnow, Poland, 2019)
Aim of the study: Chronic venous disease is frequent that affects people of various professions and ages. It consists of a set of symptoms located in the lower limbs, and edema is one of the first and most frequent signs. The aim of this study was to investigate the lifestyle influence on frequency of lower limbs swelling formation among medicine students. Materials and methods: Analysis of questionnaire conducted among 482 students of the academic year 2018/2019 from 12 Polish medicine universities. The survey questions encompass known and possible risk factors of lower limbs edema. CEAP scale was used to assess the severity of chronic venous disease. Results: Lower limb edema occurred in 30% of the respondents, of which 55% stated the exacerbation of symptoms on the days they attended classes. Conclusions: Medical students suffer from edema, it is more common among women. The type of classes affects the manifestation of lower limbs oedema. The factors that have the greatest impact on the formation of edema in students are: prolonged standing or sitting position and high ambient temperature.